1994
DOI: 10.1128/mcb.14.12.8356
|View full text |Cite
|
Sign up to set email alerts
|

The A and B isoforms of the human progesterone receptor operate through distinct signaling pathways within target cells.

Abstract: The biological response to progesterone is mediated by two distinct forms of the human progesterone receptor (hPR-A and hPR-B). In most cell contexts, hPR-B functions as a transcriptional activator of progesterone-responsive genes, whereas hPR-A functions as a transcriptional inhibitor of all steroid hormone receptors. We have created mutations within the carboxyl terminus of hPR which differentially effect the transcriptional activity of hPR-B in a cell- and promoter-specific manner. Analogous mutations, when… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

8
181
3
6

Year Published

1997
1997
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 314 publications
(198 citation statements)
references
References 34 publications
8
181
3
6
Order By: Relevance
“…In human breast cancer cells, both isoforms can function as ligand-activated transcriptional regulators of progesterone-responsive target genes; moreover, the PR-A isoform can additionally operate as a repressor of steroid hormone receptor actions. For example, progesterone activated PR-A can modulate estrogen action by preventing ER␣-mediated gene transcriptional activation as indicated by reporter gene expression (28,29). In our studies we have observed a decrease in infanticide among male mice lacking PRs, whereas a recent report by Ogawa et al (30) documented a significant increase in infanticide among male ER␣ knockout (ERKO␣) mice.…”
Section: Resultscontrasting
confidence: 55%
See 1 more Smart Citation
“…In human breast cancer cells, both isoforms can function as ligand-activated transcriptional regulators of progesterone-responsive target genes; moreover, the PR-A isoform can additionally operate as a repressor of steroid hormone receptor actions. For example, progesterone activated PR-A can modulate estrogen action by preventing ER␣-mediated gene transcriptional activation as indicated by reporter gene expression (28,29). In our studies we have observed a decrease in infanticide among male mice lacking PRs, whereas a recent report by Ogawa et al (30) documented a significant increase in infanticide among male ER␣ knockout (ERKO␣) mice.…”
Section: Resultscontrasting
confidence: 55%
“…PR activation may sustain or suppress activity in neurotransmitter circuitries that have been implicated in parental behaviors, such as those that produce vasopressin (2,25,26) and oxytocin (27). Activated PR may also modulate signaling through other steroid receptor-mediated signaling pathways, such as those mediated by estrogen receptors (ERs) (28,29). Progesterone action is mediated by two distinct forms of PR, PR-B, and the N-terminally truncated isoform, PR-A.…”
Section: Resultsmentioning
confidence: 99%
“…The human PR exists in two isoforms, a B isoform (PR-B) and an N-terminal truncated A isoform (PR-A), possessing different transcriptional capacities, despite similar hormone-and DNA-binding properties (Kastner et al, 1990;Sartorius et al, 1994;Wen et al, 1994;Richer et al, 2002). T47D cells, here referred to as T47D-WT cells, express both PR-A and -B in an oestrogendependent manner (Keydar et al, 1979;Sutherland et al, 1992).…”
Section: Resultsmentioning
confidence: 99%
“…Human PR exists as two isoforms, A and B. Altered ratios of PR isoform expression have been reported to be closely associated with modulations of various progesterone actions, [21][22][23][24] but the precise functions of PRA and PRB have not been clearly characterized. In the great majority of progesterone-responsive cells, PRB is a dominant activator of progesterone-responsive target genes, whereas PRA may inhibit this PRB activity.…”
Section: Discussionmentioning
confidence: 99%